Altered discrimination of start codons and initiator tRNAs by mutant initiation factor 3. - O'Connor, M (2001)
IF3 is essential for ensuring the fidelity of the initiation step of translation in bacterial cells. Mutations at residues R99 and R131 in the C-terminal domain of the factor have previously been shown to increase initiation from the non-canonical GUA codon. Here we show that these mutant forms of IF3 fail to discriminate against initiation from many different non-AUG codons. They also enhance the activity of mutant tRNAs carrying changes in the three consecutive G-C pairs that are conserved in the anticodon stem of initiator tRNAs. In addition, the IF3 mutants stimulate initiations from leaderless mRNAs and from internal initiation codons, in the absence of any SD-anti-SD interaction. These results indicate that IF3 ensures the accuracy of initiation by inspecting both the codon-anticodon pairing and unique features of the initiator tRNA as well as suppressing initiation from other potential start sites within the mRNA.